Development and Evaluation of Internal PMSM Cooling for Electrified Vehicles - Larsson, Johan; Lindström, Martin (My University, 2019)
Electrified vehicles are becoming more common due to tougher emission legislation and customer demands. The need for powerful, compact and efficient electric machines is therefore increasing. The aim in this study was to improve the machine, primarily with regards to these aspects while still keeping it suitable for mass production. To achieve this aim, one area of the machine was identified as having the highest improvement potential, the cooling. This improvement area was chosen after a literature study of the electric machine. An internal cooling concept was developed to replace the existing external cooling jacket solution. Several solutions were considered, the final solution uses hairpin conductors and internal water cooling. The internal cooling solution resulted in a decrease in diameter by approximately 7.9 %, and by using hairpin conductors the length of the machine was reduced by roughly 8.8 %. A CFD analysis was performed which showed an increase in thermal duty by about 70 % while reducing the pressure drop through the system by over 80 % when compared to a conventionally cooled machine. In order to achieve a robust and reliable solution, the development of the sealing as well as insulation solution has been taken into consideration. Furthermore the hairpins are coated to insulate them from the coolant. The improvements to the electric machine opens up for several design choices. The size reduction can make the packaging easier and give room for other components, alternatively, the dimensions of the internal components can be increased to get a higher performance machine with the same outer dimensions as before. An overall more efficient electric machine is beneficial with regards to driving range of the vehicle and in a broader sense, leads to a reduced environmental impact of the vehicles.
Keywords: PMSM, electric machine, internal cooling, hairpin, OpenFoam, Helyx, power density, efficiency, pressure drop, convective heat transfer coefficient